A Comparative Analysis of Potential Toxic and Essential Elements in in-situ Derived and Commercial Fish Feeds Applied in Cage Aquaculture Fish, Lake Victoria Basin, Kenya - Otieno, M. A.; Osano, O.; Marriott, A. L.; Watts, M. J. (Africa Environmental Review Journal, 2022)
The uses of feeds are critical to success of aquaculture farming on Lake Victoria Basin. The composition of the feeds can either be derived from in situ plants or animals e.g. the Caridina niloticus or Rastrineobola argentea within the basin or externally sourced from outside the catchment. The net effect from the input of those feeds from outside could increase eutrophication in the lake while feeds derived from fauna and flora from the lake may not. A potential to exploit the in-situ products compromising C. niloticus and R. argentea is immense and this may offer an environmentally sustainable feeds sources for aquaculture. The nutritional values of the in-situ based feeds and the formulated feeds from local flora and fauna within the ecosystem of the lake are compared. Samples from both the formulated and in-situ based fish feeds were collected from aquaculture farms or from local sources within the basin. The samples were then freeze-dried and ground to fine local powder and dissolved using acid digest process. The resulting sample-acid solution was then analyzed using an Agilent 7500cx inductively-coupled plasma mass spectrometer (ICP-MS). In essential element, the C.niloticus samples had higher values of 6.87 ± 1.49, 32.97 ± 6.62, Fe 942.70 ± 246.01, 137.30 ± 34.13, 0.68 ± 0.13 and 105.48 ± 16.04 mg/kg for Boron (B),Copper (Cu), Iron (Fe), Manganese (Mn), Molybdenum (Mo) and Silicon (Si) respectively compared to R.argentea. While in lower values of 1.03 ± 0.10 and Zn 181.16 ± 18.76 mg/kg were observed in the Selenium (Se) and Zinc (Zn) respectively in C. niloticus compared to R. argentea samples. In Potentially Toxic Elements (PTEs), in-situ based feeds specifically C. niloticus had significantly high PTEs of 680.76 ± 203.34, 0.99 ± 0.17, 98.56 ± 23.69 and 9.69 ± 3.21 mg/kg in Aluminium (Al), Arsenic (As), Barium (Ba) and Chromium (Cr) respectively compared to formulated feed pellets. Our study therefore; indicates that, the in-situ based feeds are potential competitors with the formulated fish feeds as they are the most promising source of animal based protein and also contain essential micronutrients and macronutrients that add nutritive value to the fish. The local cage farmers are therefore encouraged to use more often the insitu-based feeds together with the formulated feeds to add nutrients to the caged fish for human consumption.